Clinical and Radiographic Outcomes Following Management of Benign Bone Lesions of the Hand With Calcium Phosphate Bone Cement. Issue 1 (March 2022) - Jorgensen, Anna; Johnson, Jeremiah; Rodner, Craig
Abstract : Background: Enchondromas are benign primary bone tumors that often occur in the hand. Surgical curettage is often indicated for symptomatic lesions, but controversy exists regarding whether and how best to fill the void. Autograft and allograft bone in addition to various types of plaster or cement are common means addressing the postexcision defect. This study reports long-term clinical and radiographic outcomes of excision with calcium phosphate bone cement (CPC) for benign bone lesions of the hand. Methods: This is a retrospective review of symptomatic benign bone lesions treated with curettage and CPC by a single surgeon with long-term follow-up. Following Institutional Review Board approval, consenting patients returned for postoperative research visits, during which radiographs were taken and functional outcome scores were measured. Results: Of the 7 patients who consented to participate, all initially presented with pain at the site of the tumor. Average follow-up time was over 6 years and overall functional outcome scores were good with early return to work. Cementation filled nearly the entire lesion on postoperative films and there were no postoperative fractures, infections, wound problems, or revision surgeries. Conclusions: This study reports good long-term radiographic and functional outcomes, without recurrences, in a series of patients with symptomatic benign bone lesions of the hand when treated with excision and CPC by a single surgeon.